Analisis Tingkat Pengungkapan Sosial terhadap Laporan Tahunan Industri Manufaktur dan Non-Manufaktur - Budi Lesmana; Riyanto; Sakti Muda Nasution; Mira Ismirani Fudsyi; Jonathan Lucky Sasmitha (LPPM POLITEKNIK LP3I BANDUNG, 2026)
Based on the research conducted and supported by existing theories, at the 5% significance level, there is a significant difference in the level of social disclosure, with manufacturing companies reporting higher levels than non-manufacturing companies. This difference is generally due to differences in company size and operational characteristics, which influence the social impacts experienced by manufacturing and non-manufacturing companies. Hypothesis testing, taking into account the size of the sample companies, revealed a significant difference in the level of social disclosure, with manufacturing companies reporting higher levels than non-manufacturing companies with large firm sizes. There was no significant difference in the level of social disclosure for companies with small firm sizes, with manufacturing companies reporting smaller levels than non-manufacturing companies with smaller firms. A comparative study of the level of social disclosure using a content analysis method using a score approach within a specific range for each category, for example, a score between 0 and 3, where 0 indicates no social disclosure, 1 indicates minimal social disclosure, 2 indicates general social disclosure without complete explanation, and 3 indicates specific and complete social disclosure.